2005
DOI: 10.1189/jlb.0205078
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant dimeric MHC antigens protect cardiac allografts from rejection and visualize alloreactive T cells

Abstract: Monomeric and dimeric soluble major histocompatibility complex (MHC) molecules down-regulate activated T cells in an antigen-specific manner in vitro. This property could be exploited to modulate alloresponses in vivo but has remained difficult to demonstrate. Here, intraperitoneal infusion of a Lewis-derived rat MHC class I molecule, RT1.A(l)-Fc, in Dark Agouti (RT1.A(a)) recipient rats prolonged cardiac graft survival, which led to permanent engraftment. This effect was mediated by T cell impairment of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Over the last two decades induction of T cell immunity utilizing soluble pepÀ MHC-Ig in vivo has been a challenging approach resulting in different outcomes depending on the experimental set up and treatment protocol [15,17,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades induction of T cell immunity utilizing soluble pepÀ MHC-Ig in vivo has been a challenging approach resulting in different outcomes depending on the experimental set up and treatment protocol [15,17,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, soluble ligands for TCRs in multimeric form have been developed to target Agspecific T cells with increased affinity (30,31). Porto mediated by T cell impairment of target cell lysis by CD8ϩ T cells and down-regulation of interferon-␥ production by CD4ϩ T cells (16). However, Hirsch et al observed H-2K b / IgG1 successfully induces Ag-specific T cell activation in vitro and in vivo, and retards tumor growth (33,15).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, soluble ligands for TCRs consisting of engineered MHC molecules in multimeric form have been developed to target Ag-specific T cells (14,15). Like monoclonal antibodies (mAbs) directed against the TCR/CD3 complex, soluble bivalent peptide-MHC molecules are capable of delivering a signal through the TCR and result in transduction of a unique signal that leads to immune dysfunction and tolerance induction (16,17).…”
mentioning
confidence: 99%
“…Fried et al reported in 2005 that rat RT1.A-Fc dimers were able to prolong the survival time of heart grafts, suggesting the utility of soluble MHC dimers for inhibiting transplant rejection. pMHC dimer may therefore be useful for inhibiting transplant rejection (188).…”
Section: Role Of Soluble Donor Mhc-i Moleculesmentioning
confidence: 99%